School-To-Work Transition Experiences among Hospitality Graduates: A Hermeneutic Phenomenological Approach - Ling, Lui Koon (2025)
This study investigated the school-to-work transition (STWT) experiences of hospitality graduates in the selected Private Higher Education Institutes, focusing on how they have constructed, adapted, and sustained their early careers within the hospitality sector. While existing research in hospitality education has focused on employability outcomes, limited attention has been given to the emotional, social, and cultural dimensions shaping graduates' real-world transitions. The study involved 14 participants, comprising Malaysian hospitality graduates (8 females and 6 males) aged 24 to 30. Participants represented a diverse range of hospitality departments, including room divisions, food and beverage service, supporting departments, events/retails management, and revenue management. All had completed tertiary education in hospitality and had worked in at least one operational or managerial role since graduation, offering insight into both linear and non-linear career trajectories. A hermeneutic phenomenological methodology was adopted to explore participants’ lived experiences through in-depth interviews. Data were thematically analyzed in three interpretive stages aligned with the research objectives: hospitality education experiences, actual transition processes, and outcomes of transition. The analysis was guided by Gadamer’s interpretive framework of the ‘fusion of horizons,’ allowing the researcher interpretation to evolve with participants’ narratives. Findings indicate that graduates often enter the field with passion and idealism but face significant misalignments between academic preparation and workplace realities. The school-to-work transition (STWT) was marked by emotional labour, unclear job expectations, and gaps in technological and managerial competencies. Despite these challenges, many graduates developed coping strategies such as seeking informal mentorship, leveraging soft skills, and redefining career goals. Support networks, structured onboarding, and experiential learning played critical roles in fostering resilience and career sustainability. These findings directly address literature gaps by shifting attention from attrition to the experiences of those who persist in hospitality, highlighting how cultural context and post-pandemic realities shape transition outcomes. A key contribution of this study is the development of an evidence-based Conceptual Model of navigating STWT in Hospitality Graduates, integrating social cognitive career theory, experiential learning, and career development theory. Building on this, the study proposes the PIVOT Strategy - Purpose, Institutional Influence, Venture, Overcoming, and Triumph as a practical guide for enhancing STWT outcomes. This contribution extends existing career theories to the Malaysian hospitality context, providing actionable insights for curriculum development, industry partnerships, and policy interventions.